KARAKTERISASI TOKOH KUSUNOKI DALAM NOVEL MIKKAKAN NO KŌFUKU KARYA MIAKI SUGARU (TEORI ORSON SCOTT CARD) - Melvin Alfatur Farhan; Fenny Febrianty (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2022)
This study aims to analyze the characterization technique of Kusunoki in Miaki Sugaru's novel Mikkakan no Kōfuku. The method used in this research is the descriptive analysis method with the characterization analysis technique proposed by Orson Scott Card. This study uses 20 citations as a result of data findings. The results of this study indicate that several variables are forming the character of Kusunoki, namely: motives, past, reputation, stereotypes, friendship networks, habits and patterns, talents and abilities, tastes and preferences. Keywords : Characterization, Descriptive Analysis, Novel Three Days of Happiness